ドライバレー クッサク チョウサ 1973-74ネン タイ ホウコク - 鳥居, 鉄也; トリイ, テツヤ; 中井, 信之; ナカイ, ノブユキ; 倉沢, 一; クラサワ, ハジメ; 吉田, 栄夫; ヨシダ, ヨシオ; 綿抜, 邦彦; ワタヌキ, クニヒコ; 大野, 正一; オオノ, ショウイチ; et al. (国立極地研究所, 1974)
P(論文) The Japanese researches participated in the Dry Valley Drilling Project (DVDP) in the McMurdo Sound region during the 1973-1974 summer season. This project was jointly organized by New Zealand, the United States of America and Japan, and started in the austral summer of 1971-1972 with preliminary investigations-the first phase-such as seismic soundings and aeromagnetic survey, which have been completed during the season. In the first phase, the Japanese researchers undertook electrical soundings, and in the second phase-1972-1973-carried out petrographic and chemical analyses of core samples taken from No. 1 and No. 2 bore holes on Ross Island. In the survey of the Dry Valley for the third phase, the Japanese researchers took special interest in the geochemical problems. The survey party consisted of four geochemists, a geologist and a geomorphologist. A technician for thin-sectioning and a field assistant were also included in order to make the best use of instruments such as an X-ray diffractometer, a thin-sectioner, polarized microscopes, etc. which were contributed by the Japanese to the Thiel Earth Science Laboratory in the McMurdo Station. From the latter part of October, 1973, five members including a technician and a field assistant examined core samples from No. 3 hole and carried out field works at the Lake Vanda (No. 4), Don Juan Pond (No. 5) and Lake Vida (No. 6) drilling sites. During the drilling at Lake Vida in the middle of December, three new members joined the party to work in rotation with members who had arrived earlier. They examined core samples from hole No. 6 and worked in the field at the Lake Fryxell and New Harbour sites. The Japanese were particularly interested in the hydrogeochemistry of the lakes the mineralogy of the salt deposits and secondary minerals and the isotope geology of volcanic core samples. Accordingly, the field work comprised the following tasks : 1) visual observations and descriptions of core samples, 2) collection of core samples to be chemically ...